Cognition, Collective Action, and COVID-19: Managing Crises in Real Time. Issue 4 (4th July 2022) - Comfort, Louise K.
Abstract: Managing crises in real time places a distinctive burden on public managers as they encounter a gap between cognition of risk and action taken to reduce that risk. The uncertainty implicit in risk that has not yet occurred impedes actions that would reduce the risk when it does occur. In practice, actions not taken in time accelerate losses when the hazard does occur. This recurring dilemma in public management is observed acutely in the context of the rapidly escalating threat of COVID-19. This article briefly compares response operations to COVID-19 in four countries—South Korea, Italy, United States, Mexico—and documents different operational responses and different consequences in the number of confirmed cases and deaths from COVID-19 among the countries. The differences in outcomes are linked to the concept of complex time, where the threat of COVID-19 is perceived with different degrees of experience, knowledge, and urgency among the countries. The article concludes that resistance to uncertainty and failure to act is reduced by creating a structured reasoning process for consistent inquiry into unknown conditions, and timely, credible reporting of the changing threat status. Findings are documented with data from Johns Hopkins University Coronavirus Research Center, Baltimore, MD, 2020–2021.